Full adder circuit design with novel lower complexity XOR gate in QCA technology - H. Majeed, Ali; Zainal, Mohd Shamian; Alkaldy, Esam; Md Nor, Danial (Springer, 2020)
Quantum-dot Cellular Automata (QCA) is a new technology for designing digital circuits in Nanoscale. This technology utilizes quantum dots rather than diodes and transistors. QCA supplies a new computation platform, where binary data can be represented by polarized cells, which can defne by the electron’s confgurations inside the cell. This paper explains QCA based combinational circuit design; such as half-adder and full-adder, by only one uniform layer of cells. The proposed design is accomplished using a novel XOR gate. The proposed XOR gate has a 50% speed improvement and 35% reduction in the number of cells needed over the best reported XOR. The results of QCADesigner software show that the proposed designs have less complexity and less power consumption than previous designs.